INDIVIDUAL DEVICE FOR TREATMENT CONTRACTURE MANDIBLE - V. Kindiy; V. Dvornik; V. Novikov (Український стоматологічний альманах)
Despite the rapid development of dentistry there is a highly topical issue of treatment of contractures of the mandible. Contracture, persisting for a long time, remains a major cause of complaints of patients during rehabilitation.